The origins of subnational democracy: how colonial legacies and labor incorporation shaped regime heterogeneity within Latin American countries - Pérez Sandoval, J (2021)
Despite recent contributions, subnational democratic variation has received little systematic attention in comparative politics and continues to be a grave omission (Dahl 1971, 12) in the literature on democratization. Moreover, current explanations are at fault of ignoring the intricacies of time. Consequently, our understanding of the regime heterogeneity observed within countries has hitherto remained ahistorical. To overcome this and other limitations, using evidence from the largest federations of Latin America, I put forth the first comparative, and historically grounded explanation of the origins of subnational democracy.